Experimental study of the degasification efficiency of supersaturated dissolved oxygen on stepped cascades and correlation prediction model. (15th December 2021) - Cheng, Xiaolong; Lu, Jingying; Li, Ran; Feng, Jingjie; Ye, Mao; Mao, Yingzhu; Li, Kefeng
Abstract: Spills of dams often lead to dissolved gases supersaturation of water downstream. Owing to the slow dissipation, the impact of supersaturated dissolved gases in cascade hydropower development basin may be basin-wide, which can cause fish mortality. It is imperative to explore high-efficiency technology to reduce the saturation of dissolved gases. Stepped cascades are recognized as high potential air-water mass transfer exchangers, their application focused on re-oxygenation. In the literature, stepped cascades weren't applied in the dissipation of supersaturated dissolved gases yet. In this study, 89 groups of supersaturated dissolved oxygen degassing experiments were carried out in three different types of stepped cascades. From the top to the bottom of stepped cascades, supersaturated dissolved oxygen dissipated rapidly and the most significant drop was 63.3%. Degasification efficiency was defined by the percent saturation of dissolved oxygen measured on different steps and the equilibrium saturation. The variation law of degasification efficiency of supersaturated dissolved oxygen was discussed under different flow regimes. The degasification efficiency showed a positive relation with energy dissipation efficiency and the length of aerated flow region. Then a correlation model to predict the degasification efficiency was established with which the square of the correlation coefficient ( R 2 ) between calculated and experimental values is 0.93. Finally, two possible applied scenarios of stepped cascades in natural rivers were listed, the model was proved practical. The results of this study can provide suggestions for the construction, operation and management of hydropower development considering ecological-environmental protection. Graphical abstract: Image 1